Why Does Frustration Predict Psychopathology? Multiple Prospective Pathways Over Adolescence: A TRAILS Study. Issue 1 (14th December 2016) - Jeronimus, Bertus F.; Riese, Harriëtte; Oldehinkel, Albertine J.; Ormel, Johan
Abstract: Adolescents' temperamental frustration is a developmental precursor of adult neuroticism and psychopathology. Because the mechanisms that underlie the prospective association between adolescents' high frustration and psychopathology (internalizing/externalizing) have not been studied extensively, we quantified three pathways: stress generation [mediation via selection/evocation of stressful life events (SLEs)], cross‐sectional frustration‐psychopathology overlap ('carry‐over'/common causes), and a direct (non‐mediated) vulnerability effect of frustration, including moderation of SLE impact. Frustration and psychopathology were assessed at age 16 with the Early Adolescent Temperament Questionnaire and the Youth Self‐Report. No gender differences in frustration were observed. At age 19, psychopathology was reassessed by using the Adult Self‐Report, while occurrence of endogenous (self‐generated) and exogenous (not self‐generated) SLEs during the interval (ages 16–19) were ascertained with the Life Stress Interview, an investigator‐based contextual‐stressfulness rating procedure (N = 957). Half of the prospective effect of frustration on psychopathology was explained by baseline overlap, including effects of 'carry‐over' and common causes, about 5% reflected stress generation (a 'vicious' cycle with the environment adolescents navigate and shape), and 45% reflected unmediated association: a direct vulnerability effect including stress sensitivity or moderation of SLE impact. After adjustment for their overlap, frustration predicted the development of externalizing but not internalizing symptoms. Copyright © 2016 European Association of Personality Psychology